DEVELOPING PHYSICAL QUALITIES OF PRIMARY SCHOOL STUDENTS THROUGH ACTIVE GAMES IN LESSONS - Dedaxanovna, Mavlanova Obidaxon (Research Focus International Scientific Journal, 2026)
This article provides information about games specific to the development of physical qualities of primary school students and their importance.